Photoshop CS4 for dummies - Bauer, Peter 1957- (--For dummies, 2008)
Describes the basics of Adobe Photoshop CS4, discussing such topics as sizing and resizing images, choosing colors, working with layers, creating composite images, using masks and channels, and adding type.